Analysis of The Use of Learning Media in The Holistic Curriculum of IPAS Subjects At Elementary School 33 Waimnir Southwest Papua - Jusmida; Rosidah, Cholifah Tur; Rosmiati (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2024)
Learning media is one of the components in the learning process that can help teachers convey learning material so that children can have an interest in the learning material presented. This study aims to describe the results of the analysis of the Use of Learning Media in the Holistic Curriculum of IPAS Subjects at Elementary School 33 Waimnir, Southwest Papua. The research method uses a qualitative approach is a research approach that aims to understand the phenomenon in depth and thoroughly. The subject of this research is class IV (four) students totaling 17 people at State Elementary School 33 Waimnir Southwest Papua. The results stated that the right learning media is very important in supporting student learning. The selection of appropriate learning can help students to understand the learning material delivered by the teacher. Learning media can provide concrete experience and as an intermediary that helps students learn. It can be concluded that the use of learning media has a positive impact on the learning progress of SD Negeri 33 Waimnir students in Southwest Papua, including increased understanding of the material, learning motivation, and active involvement in the learning process.